Steel frames with bracing mechanism and hysteretic dampers. - Phocas, M.C.
A new earthquake resistant structural system for multi storey frame structures, based on a dual function of its bracing components, is developed. This consists of a hysteretic damper device and a cross bracing mechanism with a kinetic closed circuit, working only in tension, so that cable members can be used for this purpose. Solutions are presented regarding the connections' design of three types of structural frame system, that are concerned throughout the study : braced moment free frame, braced moment resisting frame with moment free supports, and with moment resisting supports . The dynamic behaviour of the system is investigated on the basis of an SDOF model and based on the response spectra method an approximate design approach of the controlled structures is shown. From the time history analysis of the structural systems for the El Centro earthquake the areas of appropriate stiffness relations of the frames to the hysteretic dampers and the cable braces are deduced, so that the energy distribution of the system may be controlled by the damper cable bracing mechanism. Based on the results of these studies, a predesign approach is developed for the implementation of the control system in frame structures.
Keywords: Passive control; Braced steel frame; Hysteretic damping